2021
DOI: 10.3892/etm.2021.9785
|View full text |Cite
|
Sign up to set email alerts
|

4‑Hexylresorcinol inhibits osteoclastogenesis by suppressing the NF‑κB signaling pathway and reverses bone loss in ovariectomized mice

Abstract: 4-Hexylresorcinol (4HR) is a small organic compound that is widely used as an antiseptic and antioxidant. In the present study, its role in osteoclastogenesis was investigated. Bone marrow-derived macrophages from mice were used to examine the role of 4HR in osteogenesis. An ovariectomy (OVX) mouse model was constructed to examine the effect of 4HR in vivo, followed by hematoxylin and eosin and tartrate resistant acid phosphatase staining. In the present study, 4HR effectively suppressed receptor activator of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, 4HR might have more advantages for wound healing acceleration or treatment of metabolic disease than TSA. Recently, a Chinese team found that 4HR administration increases bone mineral density in the osteoporosis animal model [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, 4HR might have more advantages for wound healing acceleration or treatment of metabolic disease than TSA. Recently, a Chinese team found that 4HR administration increases bone mineral density in the osteoporosis animal model [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 4HR administration per os may be considered for the patients having osteoporosis. Recently, China team demonstrated 4HR administration per os has a therapeutic effect on osteoporosis in the animal model [ 73 ].…”
Section: Main Textmentioning
confidence: 99%
“…Given that both types of DM are characterized by chronic inflammation and disturbances in the immune system, inhibiting the nuclear factor kappa-light-chain-enhancer of the activated B cells (NF-κB) signaling pathway could mitigate some of the foundational processes of the disease. Since 4HR has been shown to inhibit NF-κB [24,25], its administration may offer a therapeutic strategy to alleviate the disturbances induced by DM. The administration of 4HR, through its roles in enhancing wound healing [22], exerting antioxidant effects [21], inhibiting the NF-κB pathway [24,25], and reducing serum glucose levels [23], may prove advantageous in mitigating complications in the testes induced by STZ-induced DM.…”
Section: Introductionmentioning
confidence: 99%
“…Since 4HR has been shown to inhibit NF-κB [24,25], its administration may offer a therapeutic strategy to alleviate the disturbances induced by DM. The administration of 4HR, through its roles in enhancing wound healing [22], exerting antioxidant effects [21], inhibiting the NF-κB pathway [24,25], and reducing serum glucose levels [23], may prove advantageous in mitigating complications in the testes induced by STZ-induced DM. While the administration of 4HR has been shown to lower serum testosterone levels and reduce mandibular size in growing healthy rats, indicating complex effects on testosterone dynamics [26], the implications of these findings for its therapeutic use, especially in diabetic testes, remain uncertain and warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%